Analisis Kemandirian Belajar Mahasiswa Secara Daring Pada Program Studi Pendidikan Matematika Universitas Veteran Bangun Nusantara Sukoharjo Tahun Akademik 2020/2021 - Dyah Ayu Pramestisari; Dewi Susilowati; Erika Laras Astutiningtyas (Absis: Mathematics Education Journal, 2022)
The qualitative descriptive method was used to determine the level of online learning independence of students in even semester students of the Mathematics Education Study Program, Universitas Veteran Bangun Nusantara Sukoharjo for the 2020/2021 academic year. Data collection techniques in the form of questionnaires and interviews. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Checking the validity of this research data using triangulation method. The data obtained from the students learning independence questionnaires showed that the percentage of indicator 1 (self-confidence) was 78.68% so that it was included in the good category, indicator 2 (learning intiative) was 62.45% so that the category was quite good, indicator 3 (awareness of responsibility) was 84.02% so that it is in the very good category, indicator 4 (setting learming targets and objectives) is 86.44% so that it is in the very good category, indicator 5 (choosing and implementing learning strategies) is 77.94% and is in the good category. The results showed that students independen learning gave good results in online learning even though there were some obstacles. So that online learning is good fo use for the Mathematics Education Study Program, Universitas Veteran Bangun Nusantara Sukoharjo.